Radiation therapy and chemotherapy preoperative in squamous cancer advanced esophagus - Aguiar, Sergio; Delgado, Fernando; Aizen, Bernardo; Berhouet, Horacio; Lussheimer, Daniel; Luongo, Alvaro (Cirugía del Uruguay, 1995)
Esophagus cancer is a pathology that more often appears in man than in woman, of ages from 50 to 70 years, an have a strong association with exogenous factors.